Association of Mollusks with Mangroves to Support Ecotourism Development on the South Coast of Lombok Island - Samtika , Nuning; Muh Arafatir Al Jarwi; Abdul Syukur (Jurnal Biologi Tropis, 2024)
Mangroves are a type of plant that has adapted to environments that have salinity, such as in estuary areas. Mangroves that grow and develop contribute to sustainable fauna diversity, such as molluscs. Therefore, the aim of this research is to assess the diversity of molluscs associated with mangroves as a natural tourist attraction on the southern coast of East Lombok (Bale Mangrove). The methods used are belt transect and hand sorting and the data analysis used is species diversity (Shannon-Wiener), species uniformity (uniformity index), species dominance (dominance index). The research results have found 16 species consisting of three bivalves and 22 species consisting of eight Gastropods. Furthermore, there are four species of mangroves found in Bale Mangrove ecotourism, namely: Rhizopora Apiculata, Rhizhopora Mucronata, Sonneratia Alba, and Avecinea Marina. Furthermore, the index values ​​for species diversity, species uniformity and species dominance show that Bivalves have a species diversity of 1.306, while Gastropods have a species diversity of 1.016. The species uniformity of Bivalves is 0.729, while the Gastropods have species uniformity of 0.631. The dominance index for Bivalves is 0.393 and Gastropods is 0.501. Therefore, the conclusion is that the potential of mangroves with their associated biota can become a natural tourist attraction.